Search analytics for your site : conversations with your customers - Rosenfeld, Louis, ....- (Brooklyn (N.Y.) : Rosenfeld Media, 2011)
"When users search your site, they're telling you in their own words what they want from your organization. In 'Search analytics for your site, ' Lou Rosenfeld shows you how to harvest and analyze search query data to improve your site's search performance, content, navigation, metadata, effectiveness, and overall user experience"--P. [4] of cover.
How site search analytics can save your butt -- Site search analytics in a nutshell -- Pattern analysis -- Failure analysis -- Session analysis -- Audience analysis -- Goal-based analysis -- Practical tips for improving search -- Practial tips for improving site navigation and metadata -- Practical tips for improving content -- Bridging web analytics and user experience.
Includes bibliographical references and index.
Keywords: Web usage mining; Internet searching; Internet users -- Statistics -- Data processing; Web site development